Pengembangan Madrasah melalui Modal Sosial - Fatkhan Munif (Jurnal Kependidikan, 2020)
The purpose of this research is to describe the study of social capital as capital for madrasa in development of their institutions. Madrasa is an educational institution labeled as Islamic which initially did not immediately receive public attention. Many attempts have been made to obtain the legality of recognition of its existence. In addition, madrasa are educational institutions that have a close image with community contributions in the sense that madrasa cannot be separated from society. This contribution is an important asset for the survival and existence of madrasa. Madrasa in its development involves the community as the center of the progress of the institution. This community contribution is a social capital that can improve the quality of madrasa through their role and support. In the study of social capital, there are three main elements, namely trust, value and network. The three of them are related to each other and form a bond as an asset in developing madrasa. Madrasa and communities establish close relationships as a strategic step in improving the quality of educational institutions. Therefore it is necessary to have a harmonious relationship between madrasa and society so that common goals can be achieved.